PENERAPAN LEAN MANUFACTURING UNTUK MEMINIMASI PEMBOROSAN PROSES PRODUKSI CARTRIDGE HEATER DENGAN PENDEKATAN SIMULASI SISTEM PADA PT. XYZ - Monica Fidya Lestari (2021)
PT. XYZ is a manufacturing company that produces electric heaters and one of its products is Cartridge Heater. In the Cartridge Heater production process, it turns out that there are indications of waste in the production process, which causes a lack of company productivity. For this reason, this study aims to overcome these problems with the Lean Manufacturing method and provide suggestions for improvements in the form of production process designs and reductions in repair times that are more effective and efficient through system simulations that refer to Value Stream Mapping. The research begins by identifying waste in the production process with Value Stream Mapping tools, Process Activity Mapping, observation and discussion with the company. Then the determination of critical waste is carried out using 7 waste questionnaire and the results of critical waste are obtained sequentially from the highest score, namely waiting, transportation and over processing. The next step is to determine the most crucial subwaste and risk categories that must be followed up using Failure Mode and Effect Analysis (FMEA) and analyze the root causes of the problem using 5 why's analysis. The results show that with the proposed improvement recommendations, the Cartridge Heater production process time can be reduced from 3553.21 seconds to 2424.71 seconds and the total production of the repair simulation results also shows an increase in average production per month by 72,58% from the actual condition of 1495 units. to 2580 units. Keywords: Waste, Lean Manufacturing, Value Stream Mapping, Process Activity Mapping, Failure Mode and Effect Analysis (FMEA), 5 Why's